2015
DOI: 10.1007/s00339-015-9444-1
|View full text |Cite
|
Sign up to set email alerts
|

Control of charge dynamics by blending ZnO nanoparticles with poly(3-hexylthiophene) for efficient hybrid ZnO nanorods/polymer solar cells

Abstract: Photovoltaic performances of hybrid ZnO nanorods/polymer solar cells have been improved by controlling their charge dynamics through addition of ZnO nanoparticles into poly(3-hexylthiophene) (P3HT) photoactive layer. The inter-rod space of ZnO nanorod substrates is completely filled with the solution-processed ZnO nanoparticles/P3HT blends, forming homogeneous junction among the components. The optimum PCE of 1.020 % has been achieved from the device with 13 vol % ZnO nanoparticles loaded. The enhancement in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…It was observed that the uorescence decayed faster as the concentration of ZnO NPs increases in Sample B, consistent with the results in Ref. 7).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…It was observed that the uorescence decayed faster as the concentration of ZnO NPs increases in Sample B, consistent with the results in Ref. 7).…”
Section: Resultssupporting
confidence: 91%
“…Poly(3-hexylthiophene) (P3HT) is a conventional conjugated polymer applied in OSC as donor in the active layer 4,5) . As a candidate of inorganic semiconductor, ZnO is famous for its multiple nanostructures, which have high carrier mobility and ambient stability 6,7) . Photoinduced electron transfer occurs at the interface between the polymer (donor) and the inorganic semiconductor (acceptor) and results in ef cient charge separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation